2011
DOI: 10.1128/iai.01004-10
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Kidney and Spleen Cytokine Responses in Mice Challenged with Pathology-Standardized Doses of Candida albicans Mannosylation Mutants

Abstract: Cell surface polysaccharides are key determinants of host responses to fungal infection. We determined the effects of alterations in Candida albicans cell surface polysaccharide composition and gross changes in the host immune response in groups of mice challenged intravenously with five C. albicans strains at doses adjusted to give equal disease progression 3 days later. The five strains used were the parental strain NGY152, two mutants with defective cell wall mannosylation, pmr1⌬ mutant and mnt1/2⌬ mutant, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…In light of our observations, it is not clear, however, how these structures could be the consequence of late immune infiltrates. Furthermore, the translational relevance of this granulomatous reaction is in agreement with murine models of hematogenously disseminated candidiasis in which infection occurs in hosts with weak or normal immune responses (29, 30). …”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In light of our observations, it is not clear, however, how these structures could be the consequence of late immune infiltrates. Furthermore, the translational relevance of this granulomatous reaction is in agreement with murine models of hematogenously disseminated candidiasis in which infection occurs in hosts with weak or normal immune responses (29, 30). …”
Section: Discussionsupporting
confidence: 73%
“…In these models, C. albicans dissemination causes extensive disease, mostly in the kidneys, that are also characterized by multiple compact immune infiltrates (2830). In vitro studies describing the infection of peripheral blood mononuclear cells (PBMC) are complementary to animal models giving information about Candida pathogenesis in the context of human-like environments.…”
Section: Introductionmentioning
confidence: 99%
“…Modelling disseminated C. albicans infection by intravenous injection in normal mice demonstrated that fungal growth was controlled in the liver and spleen, while fungal burdens increased in the kidneys (MacCallum & Odds, 2005; Lionakis et al , 2010). In the kidneys, fungal burden increases were accompanied by increasing immune infiltrates (MacCallum et al , 2009a; Castillo et al , 2011). This did not occur in other organs.…”
Section: Host Responses During Infection and Diseasementioning
confidence: 99%
“…via lateral tail vein injection, which results in rapid dissemination of C. albicans in a reproducible fashion (67,68). Although fungal growth is controlled in the spleen and to a lesser extent in the liver, due to the presence of resident phagocytes, C. albicans causes extensive disease in the kidneys that is accompanied by increased immune infiltrates (68,69). Whereas with lower inocula tissue burdens and host responses within the kidney are controlled, with higher inocula sepsis might occur, leading to high fatality rates (67,70).…”
Section: Class 2 (Damage Occurs In Hosts With Weak or Normal Immune Rmentioning
confidence: 99%